2015
DOI: 10.1371/journal.pone.0122668
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for Distinct Coastal and Offshore Communities of Bottlenose Dolphins in the North East Atlantic

Abstract: Bottlenose dolphin stock structure in the northeast Atlantic remains poorly understood. However, fine scale photo-id data have shown that populations can comprise multiple overlapping social communities. These social communities form structural elements of bottlenose dolphin (Tursiops truncatus) populations, reflecting specific ecological and behavioural adaptations to local habitats. We investigated the social structure of bottlenose dolphins in the waters of northwest Ireland and present evidence for distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Furthermore, social structure analyses using long‐term photo‐identification data revealed that the two coastal populations were not only genetically, but also socially, distinct. This kind of social separation has been previously reported between the “ pelagic” and “ coastal” bottlenose dolphins (Oudejans, Visser, Englund, Rogan, & Ingram, ).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, social structure analyses using long‐term photo‐identification data revealed that the two coastal populations were not only genetically, but also socially, distinct. This kind of social separation has been previously reported between the “ pelagic” and “ coastal” bottlenose dolphins (Oudejans, Visser, Englund, Rogan, & Ingram, ).…”
Section: Discussionsupporting
confidence: 74%
“…These differences may be related to the difference in habitat structure and prey (Queller and Goodnight, 1989) for within-community (bold) and with individuals from other communities of bottlenose dolphins (between-community) genotyped with 10 microsatellite loci in Perth metropolitan waters, WA. (Defran and Weller, 1999;Oudejans et al, 2015;Sprogis et al, 2015). Here, individuals from the GR community (ComA) showed no residency pattern, with most identified individuals seen less than five times and LIR models indicating that individuals spent more time outside the study area.…”
Section: Community Segregationmentioning
confidence: 81%
“…Range overlap appears less frequent in other regions, with the oceanic ecotype not typically encountered nearer than a few kilometers from shore, e.g., >4 km in the Northeast Atlantic; Oudejans et al, (2015); >7.5 km in the Northwest Atlantic; Hayes, Josephson, Maze-Foley, & Rosel, (2017). However, parapatric distribution comparable to that observed in the present study has been documented in places including the western South Atlantic (Simões-Lopes et al, 2019) and the eastern North Pacific (Bearzi et al, 2009) where the coastal ecotype does not normally venture more than 3 and 1 km from shore, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct populations of nearshore (or coastal) and offshore (or oceanic) common bottlenose dolphins (hereafter referred to as coastal and oceanic bottlenose dolphins, respectively) are known to occur across the species' range (e.g., Duffield, Ridgway & Cornell, 1983; Hoelzel et al, 1998; Mead & Potter, 1995; Oudejans, Visser, Englund, Rogan, & Ingram, 2015; Rossbach & Herzing, 1999). Differences in habitat, morphology, hematology, genetics, diet, parasitic load, and behavior between the two ecotypes have been reported from multiple sources (e.g., Duffield et al, 1983; Hersh & Duffield, 1990; Hoelzel et al, 1998; Lowther‐Thieleking, Archer, Lang, & Weller, 2015; Mead & Potter, 1995; Morteo, Morteo, & Rocha‐Olivares, 2005; Perrin, Thieleking, Walker, Archer, & Robertson, 2011; Sanino & Van Waerebeck, 2008; Simões‐Lopes et al, 2019; Toth, Hohn, Able & Gorgone, 2012; Visser et al, 2010), despite suggested parapatry (Hoelzel et al, 1998) in some areas.…”
Section: Introductionmentioning
confidence: 99%